Renewable energy and the public : from NIMBY to participation - Devine-Wright, Patrick (Earthscan, 2011)
Throughout the world, the threat of climate change is pressing governments to accelerate the deployment of technologies to generate low carbon electricity or heat. But this is frequently leading to controversy, as energy and planning policies are revised to support new energy sources or technologies (e.g. offshore wind, tidal, bioenergy or hydrogen energy) and communities face the prospect of unfamiliar, often large-scale energy technologies being sited near to their homes.